ERENKÖY’DE BİR SELÂTİN CAMİİ: HAMİDİYE (GALİB PAŞA) CAMİİ - (:unkn) unknown (My University, 2018)
Hamidiye Camii XIX. yüzyılda Erenköy’de inşa edilen bir geç dönem Osmanlıselâtin camisidir. Temel atma töreni II. Abdülhamid’in cülûs yıl dönümündeyapılan caminin resmi açılışı sultanın 25. cülûs yıldönümüne yetiştirilemeyip biryıl sonra gerçekleştirilir. Camiye ilişkin bugüne kadar yapılan yayınlarda inşasüreci ve mimarı hakkında bir bilgiye yer verilmemiştir. Bu çalışmadaBaşbakanlık Osmanlı Arşivi’ndeki belgeler kaynak gösterilerek caminin inşasüreci, inşa masrafları ve mimarı ile ilgili değerlendirmeler yapılmıştır. Ayrıcayapının günümüze kadar geçirdiği onarımlar ilgili kurumların arşiv kayıtları ilekronolojik olarak anlatılmıştır.

Hamidiye Mosque is a late period Ottoman imperial mosque built in Erenkoy in the 19th Century. The ground breaking ceremony of the mosque is held on the anniversary of II. Abdulhamit's enthronement but the official opening couldn’t be finished to the 25. Enthronement of The Sultan and is held a year later. There is no information has been given about the construction process and the architecture in the publications related to the mosque. In this study, the construction process of the mosque, construction costs and architectural evaluations is done with the source of the documents from the Ottoman Archives of the Prime Ministry. In addition, repairs of the construction that made up until today are described chronologically with the archive records of the institutions.
An Imperial Mosque in Erenkoy: Hamidiye (GalibPasha) Mosque
Keywords: Kültürel Çalışmalar; Tarih